Hyperréalisme - Kultermann, Udo (Paris : Editions du Chêne, 1972)
de Andrea, John ; Bailey, William ; Beal, Jack ; Bechtle, Robert ; Close, chuck ; Eddy, Don ; Estes, Richard ; Goings, Ralph ; Graham, Robert ; Hanson, Duane ; Haworth, Jann ; Katz, Alex ; McLean, Richard ; Nesbitt, Lowell ; Pearlstein, Philip ; Pistoletto, Michelangelo ; etc.
Frans
boek